EVALUATION OF ONLINE LEARNING THROUGH LMS E-LEARNING MATHEMATICS STUDY PROGRAM PAMULANG UNIVERSITY - Arofah, Irvana (IJBLE Scientific Publications Community Inc., 2023)
This study aims to evaluate the implementation of online learning through E-Learning during the COVID-19 pandemic at the Mathematics Study Program at Pamulang University to find out the various shortcomings and problems faced by using the CIPP model approach with a focus on learning planning, learning facilities, learning processes, and learning output in online learning through LMS E-Learning. Primary data is obtained from students of the Mathematics Study Program at Pamulang University through questionnaires distributed online. The results of the evaluation research show that of the four learning components, the input component (learning facilities) is the one that has the lowest average of the others.